2020
DOI: 10.5703/1288284317106
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Approach for Designing SRMs in Composite Continuous Twin-Tub Girder Bridges

Abstract: High torsional rigidity and attractive aesthetics in construction of twin-tub girder bridges make them preferable for the design of curved bridges. However, according to the concepts associated with the term “Fracture Critical (FC)” that are in place today, all two-girder bridges are classified as having FC members (FCMs) due to their perceived lack of load path redundancy. For a steel bridge with FCMs, the fracture of any of the FCMs is assumed to result in complete catastrophic failure or significant loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Vehicle load excitation produced a higher signal-to-noise ratio than ambient excitation, providing a more explicit response to local damage [22]. Some studies showed that simple span bridges face more significant challenges and have more critical behavior than continuous span bridges due to their lack of girder continuity when damaged [29,38].…”
Section: Dynamic Characteristics In Response To Damage Scenariosmentioning
confidence: 99%
“…Vehicle load excitation produced a higher signal-to-noise ratio than ambient excitation, providing a more explicit response to local damage [22]. Some studies showed that simple span bridges face more significant challenges and have more critical behavior than continuous span bridges due to their lack of girder continuity when damaged [29,38].…”
Section: Dynamic Characteristics In Response To Damage Scenariosmentioning
confidence: 99%